Implementation of Clean and Healthy Living Behavior for PAUD School Children: Id - Aulia, Sayyida; Elvandari, Milliyantri (Universitas Ibn Khaldun Bogor, 2024)
PHBS in the school environment is realized to maintain cleanliness in the surrounding environment and is able to teach students very precisely by teachers so that children can maintain cleanliness wherever the child is, such as at school, at home or when the child travels. According to the Ministry of Health, Clean and Healthy Living (PHBS) is a health action carried out with awareness, aimed at ensuring that family members can help themselves in the health sector. The research method used in this research is descriptive qualitative. The use of a qualitative approach was used to gain an in-depth understanding of the implementation of clean and healthy living behavior among children at PAUD KB Anugerah, Sambas Regency, West Kalimantan. The following are some of the PHBS activities carried out by PAUD KB Anugerah, namely: facilitating PHBS support needs, eradicating mosquito larvae in the school environment, maintaining personal hygiene, and eating healthy, balanced nutrition. PHBS is implemented very well and consistently ensures the cleanliness of the school environment through consistent attention from the principal, teachers, students and everyone in the school environment. Maintaining personal hygiene, food intake, and maintaining a clean environment are very helpful to instill in young children. That way, children can practice it as a habit until they grow up.